Report of a Working Group on Forages: Tenth meeting, 28-29 April 2010, Poel Island, Germany - Maggioni, L.; Veteläinen, M.; Willner, E.; Lipman, E.; Bioversity International (2011)
The Tenth meeting of the ECPGR Working Group on Forages was held on 28-29 April 2010 on the Island of Poel, Germany and was hosted by the Leibniz Institute of Plant Genetics and Crop Plant Research (IPK), Gatersleben. The meeting gathered together Working Group members, Central Forage Database Managers and numerous observers.Since the 1990s the Working Group has been working towards the sharing of responsibilities in conservation and management of European forage collections. Specific mechanisms for identifying the most original samples (MOS) and holders of primary collection (PRIMCOLL) have been developed to identify forage accessions for the European Forage Collection (EFC). The present meeting reviewed achievements to date and made important decisions to complete the process to identify the unique European forage accessions and thus promote the goals of the initiative for “A European Genebank Integrated System” (AEGIS). The status of the European Central Forage Databases and their relationship to the European Plant Genetic Resources Catalogue (EURISCO) were presented and discussed. It was decided to use EURISCO as a starting point when updating information in the Central Forage Databases. In order to rationalize the identification of accessions for the EFC and reduce the workload when updating databases, it was also decided to merge several of the Central Forage Databases on the basis of the genus and the type of forage crop. Responsibilities were assigned for the resulting 11 databases. Several presentations dealt with on-farm and in situ conservation, and the Working Group decided to promote in situ conservation of forage crops in order to complement ex situ conservation work. The Working Group on Forages, of which many members are plant breeders, also emphasized the importance of the inclusion of forage crop-specific descriptors and characterization and evaluation data in Central Forage Databases.